Trends of Serum Electrolyte Levels toward Severity Rates in COVID-19 Patients with Type 2 Diabetes Mellitus Comorbidity in Dr. Soetomo Hospital Surabaya - Hamidah, - (Academia Nacional de Medicina, 2022)
Background: Coronavirus Disease 2019 (COVID-19) causes a lot of morbidity and mortality. More than three-quarters of hospitalized patients experience complications in the kidneys such as acute kidney injury, proteinuria, hematuria, and electrolyte imbalance. The study addressed to get an overview of the profile of serum electrolyte levels and the severity trend of COVID-19 patients with comorbid Type 2 Diabetes (DM) at Dr. Soetomo Hospital, Surabaya. Methods: This retrospective descriptive study used secondary data from medical records of COVID-19 patients with Type 2 diabetes mellitus comorbid at Dr. Soetomo Hospital, Surabaya period April – September 2020. Result: Our study revealed 103 patients with COVID-19 with Type 2 DM comorbidity. The proportion of COVID-19 patients with comorbid Type 2 DM in Dr. Soetomo Hospital, Surabaya is 17.03 %. The percentage of patients with hyponatremia, normonatremia, hypernatremia, hypokalemia, normokalemia, hyperkalemia, hypochloremia, normochloremia, hyperchloremia were 52.48 %, 45.54 %, 1.98 %, 29.7 %, 49.5 %, 20.79 %, 33.33 %, 61.62 %, 5.05 %, respectively. There found 32 % of patients with COVID-19 with mild symptoms, 18.4 % moderate, 20.4 % severe, and 29.1 % critical. The critical severity case increases in hyponatremia, hypokalemia, and hypochloremia conditions. Conclusion: The severity of COVID-19 in patients with comorbid Type 2 DM is influenced by the laboratory values and the electrolyte change. The elevated laboratory values and the decreased electrolyte levels followed by the increased severe COVID-19 case.